Genetic improvement and related activities. improvement of individual characters. yield potential - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Primary emphasis is being placed on a search for genotypes with erect architecture adapted to narrow row spacings and high populations and which show marked yield increases under intensive agronomic management. This research strategy is complemented by studies on specific problems such as exploitation of late maturity; effects of seed size on tissue cell size, drought tolerance, and leaf photosynthetic rates; and possible inefficiencies in pollination. The results are included in table form. (CIAT)